Solar Villages: Evaluating the Economic Benefits of China’s Rural Electrification Programs - Utkina Margarita Sergeevna (Journal of Islamic Economics and Business, 2026)
Rural solar-based electrification has become an important instrument for expanding energy access while promoting socio-economic development in rural areas. This study aims to examine the impact of rural solar electrification programs in China on household income, education, and public health. The study employs a quantitative approach with a quasi-experimental design, combining Difference-in-Differences (DiD) and Propensity Score Matching (PSM) to compare socio-economic changes between areas receiving electrification interventions and comparable control areas with similar initial characteristics. The findings indicate that rural electrification has a positive effect on household income, particularly non-farm income, and contributes to improvements in educational attainment and health outcomes. More specifically, electrification is associated with increased years of schooling, higher school participation, and longer study time among children, while also reducing the incidence of respiratory illness and improving households’ perceived health status. These findings suggest that rural solar electrification serves not only as a means of providing energy access but also as a broader development instrument that expands economic opportunities, strengthens human capital, and enhances rural welfare. Therefore, rural electrification policies should be integrated with local economic development, education, and health programs to maximize their long-term, sustainable benefits.